2022
DOI: 10.1159/000522020
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Neuropsychiatric and Neuropsychological Assessment Tools to Make a Differential Dementia Diagnosis in the Presence of “Long-Haul” COVID-19

Abstract: The longer term neurocognitive/neuropsychiatric consequences of moderate/severe COVID-19 infection have not been explored. The case herein illustrates a complex web of differential diagnosis. The onset, clinical trajectory, treatment course/response, serial neuroimaging findings, and neuropsychological test data were taken into account when assessing a patient presenting 8 months post-COVID-19 (with premorbid attention-deficit hyperactivity disorder, diabetes mellitus, mood difficulties, and a positive family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…[8]). Darüber hinaus stellt sich das Problem, kognitive Störungen bei Long-COVID Syndromen von denen einer beginnenden Demenz mittels TPU zu unterscheiden [9,10] oder die langfristigen Verläufe kognitiver Störungen durch wiederholte TPU zu begleiten [11,12]. Zu berücksichtigen ist auch, dass durch Quarantänemaßnahmen geänderte Lebensbedingungen sich auf die Ausprägung neuro-kognitiver Störungen auswirken können [13].…”
Section: Methodenunclassified
“…[8]). Darüber hinaus stellt sich das Problem, kognitive Störungen bei Long-COVID Syndromen von denen einer beginnenden Demenz mittels TPU zu unterscheiden [9,10] oder die langfristigen Verläufe kognitiver Störungen durch wiederholte TPU zu begleiten [11,12]. Zu berücksichtigen ist auch, dass durch Quarantänemaßnahmen geänderte Lebensbedingungen sich auf die Ausprägung neuro-kognitiver Störungen auswirken können [13].…”
Section: Methodenunclassified
“…Elderly patients are among the most vulnerable populations facing COVID-19 infection. Cognitive complaints are frequent in elderly patients after COVID-19 [ 51 , 52 ] and verse versa, patients suffering from dementia are at higher risk of COVID-19 infection and higher risk of severe forms and hospitalization [ 53 ]. The meta-analysis on the risks associated with COVID-19 infection showed that suffering from dementia increases by 2 to 3 the risk of contracting COVID-19 compared with patients of comparable age [ 54 ].…”
Section: Predictors Of Post-covid Neurological Complicationsmentioning
confidence: 99%
“…It is interesting to observe that these injuries are shared with some neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), optic neuritis and multiple sclerosis. Of interest, some authors have advanced the hypothesis that SARS-CoV-2 infection can cause the development or progression of neurodegenerative diseases (Light 2022 ; Zarifkar et al 2022 ). Once again, the link between SARS-CoV-2-induced disorders and neurodegenerative diseases is being questioned.…”
Section: Neurological Consequences Of Long-covid-19mentioning
confidence: 99%